PENGARUH FAKTOR FUNDAMENTAL MAKRO DAN MIKRO PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Pada Industri Pulp and Paper yang terdaftar di BEI) - Sari, Retty Purnama; Romli, Harsi; Marnisah, Luis (Universitas Indo Global Mandiri Palembang, 2020)
This research aims to know the impact of macro fundamental factors such as interest rate (SBI), kurs and gross domestic product; and micro fundamental factors such as return on asset (ROA), debt to equity ratio (DER) and price earning ratio (PER) on firm value in pulp and paper industry that listed in Indonesian Stock Exchange. This research used multiple regression analysis and processed with Eviews version 8. The results of study is: 1) By partial, just interest rate have negative and no significant effect on firm value, other factors such as kurs and gross domestic products, return on asset, debt to equity ratio and price earning ratio have positive and no significant effect on firm value; 2) By Simultaneous macro fundamental factor have positive and significant effect on firm value, also micro fundamental factors have positive and significant effect on firm value; 3) By Simultaneous macro and micro fundamental factors have positive and significant effect on firm value.Â Keywords: macro fundamental factor, micro fundamental factor, firm value